(untitled) (London Journal of Medical and Health Research, 2024)
A systematic review and meta-analysis of research data on the effectiveness of the drug Wobenzym in the treatment of chronic bacterial prostatitis was performed. The aim of this study to evaluate the effectiveness of Wobenzym in the complex therapy of chronic bacterial prostatitis. The analysis included randomized and non-randomized controlled studies of the effectiveness of Wobenzim in the complex therapy of chronic bacterial prostatitis. The search was carried out in the databases CENTRAL, PubMed, ICTRP, eLibrary, ClinicalTrials.gov., Google Scholar, CyberLeninka, search engines. The meta-analysis was conducted using the recommendations of the Cochrane Handbook for Systematic Reviews of Interventions. Statistical heterogeneity was assessed using the Cochran test and visually when constructing forest plots. A random effects model and a fixed effect model were used. Works published over the entire period were analyzed, 712 publications were identified, of which 9 fully met the stated criteria, all studies were non-randomized controlled. The final analysis included the results of 1292 patients. Meta-analysis demonstrated the superiority of complex therapy including Wobenzym compared to therapy without Wobenzym in all studied parameters; eradication of the pathogen, decreased quality of life (QoL) scores, an increase in the linear speed of blood flow in the veins and peak systolic blood flow velocity in the arteries of the prostate gland, maximum urine flow rate, reduction in the number of points of the NIH-CPSI "Pain" subscale (difference 5 points) and NIH-CPSI "Quality of Life" subscale. The use of therapy including Wobenzym in patients with chronic prostatitis leads to a greater increase in the number of CDA+, CD8+ lymphocytes, phagocytic activity of lymphocytes, the level of complement CH-100 and immunoglobulins M, G, A. A systematic review/meta-analysis revealed an evident, significant, positive effect of the drug Wobenzym in the complex therapy of patients with chronic bacterial prostatitis, which is associated with its pathogenetic orientation in relation to this group of patients.